Creación de una empresa dedicada al diseño, ensamblaje y comercialización de compresores de aire - Gudiño Pabón, Carlos Patricio (2018)
Like a contribution to the productive matrix change, import substitution, entrepreneurship development and innovation, encouraged by the Ecuadorian Government, the project proposes the manufacture and assembly of air compressors in the country. The objective is the domestic production development, initiate a business plan for the design, production and marketing of air compressors; propose strategies for startup a company, generating means for Ecuadorians, reaffirming the industry as the backbone of a country is economic growth. The project generates 14 jobs directly, 100 percent Ecuadorian labor, make a high positive impact and increases the national industry. According to the economic and financial analysis for the business plan, the internal rate of return has greater value than the discount rate, showing a viable project. If the IRR is 31,14 percent and the CAPM of 30.50 percent it means that the project is profitable and if we add that to the investor IRR is compared with the WACC of 18.82 percent, 70,63 percent be confirms the feasibility of the business plan. The project generates utility from the third year of the project, what is acceptable for new business. This plan is the start of new projects and related studies, which help to the proposed improvements and reach the implementation.